Echocardiographic Characteristics of Left Ventricular Diastolic Dysfunction among Impaired Glucose Tolerance Patients - Bhuiyan, AKM Mohiuddin; Sultana, Zakia; Khan, Md Fazlul Kader; Rahman, Abu Foyez M Motiour; Ahsan, M Razib; Rahmam, Md Mukhlesur; Hasan, KAM Mahbub; Haq, M Touhidul (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: The measurement of left ventricular diastolic dysfunction is important among the impaired glucose tolerance patients. Objectives: The purpose of the present study was to see the echocardiographic characteristics of left ventricular diastolic dysfunction among impaired glucose tolerance patients. Methodology: This cross sectional study was carried out in the Department of Cardiology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh from July 2005 to June 2007 for a period of two (02) years. Patients with impaired glucose tolerance (IGT) patients attending Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka, Bangladesh and fulfilled selection criteria were included in this study as group A. The apparently healthy persons without cardiovascular disease were taken as group B. All the study subjects underwent 2D and M-mode echocardiography for chamber enlargement, ventricular hypertrophy and ventricular systolic function according to recommendation of American Society of Echocardiography. Result: 2D and M-mode echocardiographic characteristics were compared between groups. Among the parameters, LA size in the group A was 31.18±3.49 mm and in group B was 25.22±4.95 mm which was significantly higher (p<0.01) in the case group. LA size was also compared among left ventricular diastolic dysfunction (LVDD) present and absent group, which was (32.76±4.61 vs 28.79±4.11 mm, p<0.001) significantly higher in the LVDD present group. Conclusion: In conclusion there is a significant differences of echocardiographic characteristics of left ventricular diastolic dysfunction among impaired glucose tolerance patients. Journal of National Institute of Neurosciences Bangladesh, 2020;6(1): 38-42